2011
DOI: 10.1289/ehp.1002727
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Chemicals in Pregnant Women in the United States: NHANES 2003–2004

Abstract: BackgroundExposure to chemicals during fetal development can increase the risk of adverse health effects, and while biomonitoring studies suggest pregnant women are exposed to chemicals, little is known about the extent of multiple chemicals exposures among pregnant women in the United States.ObjectiveWe analyzed biomonitoring data from the National Health and Nutritional Examination Survey (NHANES) to characterize both individual and multiple chemical exposures in U.S. pregnant women.MethodsWe analyzed data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
562
19
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 819 publications
(634 citation statements)
references
References 26 publications
48
562
19
5
Order By: Relevance
“…Our observed urinary BPA concentrations were similar to those measured in other studies with pregnant women. 3,45,46 Children's urinary BPA concentrations at 1, 2, and 3 years of age were higher than concentrations reported for adults but were slightly lower than concentrations observed among 6-to 11-year-old children in previous studies. 47,48 Higher BPA concentrations in children could be attributable to pharmacokinetic factors or increased food consumption per unit of body mass.…”
Section: Discussioncontrasting
confidence: 63%
“…Our observed urinary BPA concentrations were similar to those measured in other studies with pregnant women. 3,45,46 Children's urinary BPA concentrations at 1, 2, and 3 years of age were higher than concentrations reported for adults but were slightly lower than concentrations observed among 6-to 11-year-old children in previous studies. 47,48 Higher BPA concentrations in children could be attributable to pharmacokinetic factors or increased food consumption per unit of body mass.…”
Section: Discussioncontrasting
confidence: 63%
“…Pollutants come from several different sources, move on the environment and eventually accumulate in the food chain. Daily exposure to environmental persistent pollutants results in detectable levels of metals, PCBs and organochlorine pesticides in woman bodies (Woodruff et al, 2011). During pregnancy, the pollutants accumulated by the women can reach the fetus crossing the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have previously shown that environmental chemicals have been detected in virtually all pregnant women in the USA (e.g., Woodruff et al 2011b) with animal and human evidence suggesting links between chemical exposures and reductions in fetal growth (Fei et al 2008;Washino et al 2009;Kodavanti et al 2010;Harley et al 2011). In vivo and in vitro animal studies, for example, show adverse developmental and reproductive effects from chemicals such as brominated flame retardants found in consumer products (Schecter et al 2005).…”
Section: Chemical Presence In Bodiesmentioning
confidence: 99%